Nigerian Government and Religion - NGBEA , Gabriel Terwase (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
The Nigerian constitution does not explicitly mention that Nigeria is a secular State and the phrase “Secular State” is not used anywhere in the constitution. It is in the light of this constitutional provision that Nigerians are divided over the interpretation of section 10 of the constitution. Which state’s that; “The Government of the Federation or of a State shall not adopt any religion as State religion”. Instead of the Nigeria government preserving and promoting the secular status of a multi-religious and multi-ethnic society, the Nigerian government and politicians have adopted Christianity and Islam as state religions as against the even ambiguous section 10 of the constitution. Nigerian government policies practices and some official pronouncements make the Nigerian government the patron of Christianity and Islam. The Nigerian government at various times or the other has been seen to have pitched tents with Christianity and Islam at the expense of other religions in the country. Religion has become a tool in the hands of the government and the ruling class to divert attention and gain support from the electorates this paper seeks to examine the undue romance between the Nigerian government and Religion which has caused more harm than good. The Nigerian state for some time now has become an active participant in religious affairs and incapacitated itself in maintaining fairness and equity in its relation with Religions. Amongst others, the paper recommends that the role of the Nigerian government in religious matters is not healthy for peace and development. There is an urgent need for the Nigerian government to maintain a neutral posture with regard to all religions in Nigeria. The methodology adopted is historical and phenomenological, using secondary data collection and analysis done qualitatively.